Safety Measures under the Laws of Countries in the Anglo-Saxon System (United States, United Kingdom) - BAKISHEV, Kairat Alikhanovich; NURBOLATOV, Azamat Nurbolatovich; BAYSEITOVA, Aliya Temirhanovna; KEGEMBAYEVA, Zhanar Amanzhanovna; BISSENGALI, Liliya (Journal of Advanced Research in Law and Economics, 2016)
The paper argues that a clear and well-defined safety measures system can be found currently in the Anglo-Saxon legislations of the United States and United Kingdom. The article analyses safety measures aimed at protecting the public from the criminals. Particular features of safety measures that allow isolating certain categories of persons due to their ‘dangerous condition’ contribute to explaining why the system of safety lacks a clear definition. The article also examines the history of two legal systems and serves as a study into a legislative and executive conflict of safety measures definition in the United States and United Kingdom.